The effect of butterfly pea flower (Clitoria ternatea) extract gel on TNF-α and caspase-3 expression in wound tissue of wistar rats - Yulisa Afriani Ninasara; Joko Wahyu Wibowo; Israhnanto Isradji (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Exposure to acute ultraviolet B (UVB) damages the skin through oxidative stress, inflammation, and apoptosis. UVB increases the production of reactive oxygen species (ROS), which damage cells and trigger inflammation by increasing TNF-α levels. Increased ROS and TNF-α levels activate caspase-3, which causes cellular apoptosis. This damage worsens skin conditions, triggers premature aging (photoaging), and increases the risk of skin cancer. In Indonesia, approximately 57,3% of the population is exposed to sunlight, with a prevalence of dry skin ranging from 50% to 80%, while photoaging contributes to approximately 80% of the adverse effects of skin aging. Clitoria ternatea contains bioactive compounds with antioxidant and anti-inflammatory properties that have the potential to suppress caspase-3 activation and prevent cell damage. This experimental study used a post-test-only control group design with a completely randomized design, involving male Wistar rats divided into four treatment groups (K1–K4). The study was conducted at the Chemistry Laboratory of IBL UNISSULA, with animal treatment at the Animal Experiment Laboratory of IBL UNISSULA and skin tissue sample analysis at the General Medical Laboratory of CITO Yogyakarta from December 2024 to February 2025. Clitoria ternatea extract gel was applied topically once a day for 7 days, followed by UVB exposure (160 mJ/cm²) for ±15 min per day. Skin tissue samples were collected 24 h after the last treatment with a 6 mm punch biopsy, and the expression of TNF-α and caspase-3 was analyzed using qRT-PCR. Data were tested using one-way analysis of variance (ANOVA). Results, the group given a 5% dose of gel (K3) showed a significant decrease in the expression of TNF-α (0,35±0,20) and caspase-3 (0,16±0,32) compared to other groups, while the 10% dose (K4) showed no significant difference. The conclusion, Clitoria ternatea extract gel at a 5% dose effectively reduced the expression of TNF-α and caspase-3 in the skin of UVB-exposed mice.